The Role of Strategic Planning in Improving the Quality of Management of Education Organizations - Susisofianti; Hendri Gunawan; Januar; Supratman Zakir (International Journal of Education Management and Religion, 2025)
: This study analyzes the role of strategic planning in improving the quality of management in Islamic education organizations. Using a library research approach, the study examines various literatures related to strategic planning and Islamic education management. The findings indicate that strategic planning is essential in shaping the vision, mission, and long-term objectives of educational institutions, leading to improved operational efficiency, resource management, and the overall quality of educational services. However, the implementation of strategic planning in Islamic education institutions faces significant challenges, including limited resources and resistance to change. These obstacles hinder the effectiveness of strategic initiatives and long-term institutional development. To address these issues, strong support from stakeholders, including policymakers, educators, and administrators, is crucial. Additionally, enhancing managerial capacity through training and professional development programs is necessary to ensure that strategic planning is effectively implemented and sustained. This study highlights the need for a more structured and adaptive approach to strategic planning in Islamic education organizations to enhance institutional performance and long-term sustainability. By addressing these challenges, Islamic education institutions can develop more effective management strategies that align with their educational and organizational goals.